The dynamics of burnout among Slovenian primary school teachers over the school year in relation to their perceptions of various predictors of burnout in the school context - Markelj, Neja; Kovač, Marjeta; Jurak, Gregor (Frontiers in Psychology, 2023)
This study examined the dynamics of teacher burnout over the course of the school year in relation to individual and environmental factors in the school context based on a three-wave panel design using an MBI-ES questionnaire and a self-constructed inventory to measure individual and environmental factors of burnout. The sample consisted of 718 teachers from 32 Slovenian primary schools; 163 of them participated in all measurements. The major limitation of this study is the high attrition rate. However, attrition analysis showed no significant differences between the initial sample and the panel group on background variables and burnout dimensions or on environmental and individual factors. Burnout was present but not pronounced among participating teachers: Emotional exhaustion was moderately high and depersonalization and personal accomplishment were low. Over the course of the school year, burnout did not increase consistently and gradually; we found only a statistically significant increase in personal accomplishment in the middle of the school year and a statistically significant greater sense of burnout at the end of the school year. As stress accumulates over time, we would expect burnout to increase. We hypothesize that participants reduced the effects of stress through various coping strategies and/or replenish their resources. We believe that the school year is not long enough for burnout to develop. The number of stressors perceived by teachers was significantly related to burnout rates. Teachers experience stress, especially in work not directly related to teaching, and from their own performance expectations. Multivariate regression analyses yielded three different but similar models of predictors of burnout that explained 25% to 50% of the variance in teacher burnout. Regardless of the instability of the models, the time and energy demands of working with students, teacher characteristics, and classroom management are the stable antecedents in the predictor models of teacher burnout.